PARTAI DEMOKRASI INDONESIA PERJUANGAN DALAM PERSAINGAN POLITIK DI BALI TAHUN 1999-2019 - Pebriana, I Wayan Agus (Jurnal Ilmiah Widya Sosiopolitika, 2021)
ABSTRACK This study seeks to reveal the Indonesian Democratic Party of Struggle (PDI-P) in the political competition in Bali in 1999-2019. The change in the power system from the New Order to the Reformation has resulted in significant changes in the political system. At the local political level in Bali there is a shift in political power. Previously, during the New Order era, political power was controlled by Golkar, now it has begun to shift to the PDI-P. The problems discussed in this study are (1) how was the PDI-P's role in political competition in Bali from 1999-2019 (2) Why PDI-P managed to emerge as a competitor in political competition in Bali (3) What was the competition from the success of the PDI -P emerged as the dominant party in Bali. This study uses historical theory, especially historical explanations and historical cause and effect as well as theoretical assistance from social science, namely Leadership from Antonio Gramsci. The results show that throughout the post-New Order election, PDI-P managed to emerge as the dominant party in Bali from 1999-2019. The success of the PDI-P to emerge as the dominant party in Bali is inseparable from the success of the PDI-P in utilizing the symbolic capital of the past as Soekarno's party, the PDI-P has also succeeded in building a system of alliances with various community groups that provide political support, and the PDI-P has succeeded in reforming the system. party organization. this had implications for the success of the PDI-P in realizing the party's agenda. Keywords: PDI-P, Election, Political Competition, Domination